The concept of the hero in the prose of neorealism (on the example of M. Zemskov's novel «Gabriel's Saxophone») (Eurasian Journal of Philology Science and Education, 2023)
The article analyzes M. Zemskov's novel «Gabriel's Saxophone», reveals significant features and principles of new realism. This direction firmly occupies its niche in the modern cultural field of accessible, fascinating and at the same time high-quality prose. The works of Mikhail Zemskov are distinguished by a deep statement of the fundamental problems of human existence, the study of the deep contradictions of man and modern society. In his works, Mikhail Zemskov raises the problem of the degradation of society, which is interconnected with the process of changing culture. The perception of reality occurs through the author's reflection. Fragmentation of the narrative, mosaicism are a certain author's technique, which is why there is no fixed end in the hierarchy of the novel.